Evaluation of Net Energy, Standardized Ileal Digestible Lysine, and Soybean Meal Content Interactions in Pigs from 25 to 50 lb using a Central Composite Design - Hilario M. Cordoba; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt; Henrique S. Cemin; Jose A. Soto (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 4,681 pigs (PIC 337 × 1050; initially 28.7 ± 2.00 lb) were used in a 21-d trial to investigate the interaction of net energy (NE), standardized ileal digestible lysine (SID Lys), and soybean meal (SBM) content on growth performance of nursey pigs. Pigs were housed in mixed-gender pens with 35 pigs per pen and assigned in a randomized complete block design to 15 dietary treatments using a circumscribed central composite design (CCD). Factorial and axial points had seven repetitions, and the central points had a total of 24 repetitions. Eight diets were formulated to various levels of NE, SID Lys, and SBM and blended to create the 15 dietary treatments. The NE ranged from 1,059 to 1,253 kcal/lb, SID Lys from 1.08 to 1.52%, and dietary SBM content from 25.5 to 35.9%. Diets were corn-soybean meal based and soy hulls and soybean oil were added to reduce or increase NE content of the diet. Feed-grade amino acids and SBM were used to adjust SBM and SID Lys content and to maintain SID Thr, Trp, Met, Val, and Ile ratios relative to SID Lys. Increasing NE decreased (linear, P < 0.10) ADG and ADFI while F/G became poorer (quadratic, P < 0.10) due to a reduction in SID Lys:calorie ratio. There was a significant interaction (P < 0.10) observed between SID Lys and SBM for F/G, where SID Lys improved F/G, but maximized F/G when SID Lys and SBM were at 1.52% and 35.9%, respectively. When increasing SID Lys, ADG and F/G improved (quadratic, P < 0.10) up to approximately 1.43% with minor benefit thereafter. Increasing SBM content improved (linear, P < 0.10) ADG and F/G when included up to 33.8% without additional improvements thereafter. Feed cost per pig increased (linear, P < 0.10) as NE and SID Lys concentrations increased. Feed cost per lb of gain increased (quadratic, P < 0.10) as NE, SID Lys, and SBM content increased; however, there was an interaction (P < 0.10) between SID Lys and SBM where increasing both at the highest inclusion reduced feed cost per lb of gain. Revenue increased (linear, P < 0.10) as the SID Lys level and SBM content increased. Income over feed cost (IOFC) increased when increasing SID Lys (quadratic, P < 0.10) and SBM (linear, P < 0.10) levels were fed, and decreased (linear, P < 0.10) with increasing NE. In conclusion, using a CCD, increasing SID Lys resulted in a quadratic improvement in ADG and F/G with a greater response observed when SBM also increased in the diet.
Keywords: growth performance; late nursery; lysine; net energy; soybean meal